Identification of Jmjd3 as an Essential Epigenetic Regulator of Hox Gene Temporal Collinear Activation for Body Axial Patterning in Mice - Zhang, Feng; Zhao, Xiong; Jiang, Runmin; Wang, Yuying; Wang, Xinli; Gu, Yu; Xu, Longyong; Ye, Jing; Chen, Charlie Degui; Guo, Shuangping; Zhang, Dawei; Zhao, Daqing (Frontiers in Cell and Developmental Biology, 2021)
Body axial patterning develops via a rostral-to-caudal sequence and relies on the temporal colinear activation of Hox genes. However, the underlying mechanism of Hox gene temporal colinear activation remains largely elusive. Here, with small-molecule inhibitors and conditional gene knockout mice, we identified Jmjd3, a subunit of TrxG, as an essential regulator of temporal colinear activation of Hox genes with its H3K27me3 demethylase activity. We demonstrated that Jmjd3 not only initiates but also maintains the temporal collinear expression of Hox genes. However, we detected no antagonistic roles between Jmjd3 and Ezh2, a core subunit of PcG repressive complex 2, during the processes of axial skeletal patterning. Our findings provide new insights into the regulation of Hox gene temporal collinear activation for body axial patterning in mice.